Effect of glycemic control on diabetic retinopathy and diabetic macular edema: a prospective observational study - S., Kajal Seema; T., Jayalekshmi; S., Manasa; M., Prasenna (International Journal of Advances in Medicine, 2021)
Background: The objective of the study was to examine the effect of long-term glycemic control, as measured by glycated hemoglobin levels (HbA1C), on the onset and progression of diabetic retinopathy (DR) and diabetic macular edema (DME) over a period of 10 years. Methods: Patients who were diagnosed to have type 2 diabetes mellitus participated in this cross-sectional observational study. Duration of onset of diabetes and the glycemic control status were analyzed. Fasting and postprandial blood sugar levels and HbA1C levels were tested for every participant. Diabetic retinopathy was graded as per the ETDRS guidelines using stereoscopic fundus photographs. In addition to the clinical evaluation, optical coherence tomography was done to confirm the presence of DME. Results: A total of 212 diabetic patients were enrolled in this study. One sixty-four patients (78.1%) had DR, out of which 71 patients (43.3%) had mild non proliferative diabetic retinopathy (NPDR), 42 patients (25.6%) had moderate NPDR, 31 patients (18.9%) had severe NPDR, and 20 (12.2%) had proliferative diabetic retinopathy (PDR). Fifty-nine patients with DR (36%) had DME. Duration of diabetes (14.62±6.18 vs 9.72±3.68 years, p<0.001), higher fasting blood glucose (176.79±59.13 vs 138.46±49.44 mg/dl, p<0.001) and higher HbA1c levels (8.21±1.38 vs 7.48±1.25 %, p=0.002) were significantly associated with DR. Conclusions: The stage of diabetic retinopathy rather than metabolic status is a strong predictive factor for the development of diabetic macular edema.